Dentro e fora da valise: histórias da meia noite, de Machado de Assis - Seidel, Vizette Priscila [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This work reflects on the selection made by Machado de Assis to compose his Histórias da meia-noite. During this process, he chose certain texts that were published between 1870 and 1873, in the Jornal das Famílias, excluding a significant number of them. We researched the possible reasons for the writer’s selection, trying to observe if these choices follow any literary project of the author. In order to do so, we have examined critical readings of Machado’s works, the short stories in their medium of primary publication and theoretical references of Cultural History. We aim to contribute to the advancement of researches on Machado de Assis’ short stories, regarding the construction of these texts and configuration, by his own choice, of his literary project, as well as the possible relation between the formation of this collection and the ideal of “Brazilian literature” that the writer and critic Machado de Assis seemed to have in mind at that moment. Facts related to the history of the collection’s publication were also analyzed, in order to verify if the editor Baptiste-Louis Garnier, also the publisher of Jornal das Famílias and the collection Histórias da meia noite, of 1873, would have participated – directly or indirectly – in the selection made by the author from Rio de Janeiro

Este trabalho reflete sobre a seleção dos contos que Machado de Assis fez para compor suas Histórias da meia-noite. Na montagem, escolheu certos textos que havia publicado entre 1870 e 1873, no Jornal das Famílias, desconsiderando um número significativo deles. Investigamos as possíveis razões para a seleção que o escritor montou, tentando observar, ainda, se tal escolha obedece a algum projeto literário machadiano. Para tanto, recorreu-se a leituras da crítica machadiana, aos contos em seu suporte de publicação primária e ao referencial teórico da História Cultural. Almeja-se contribuir para o avanço das pesquisas a respeito dos primeiros contos machadianos, no que concerne à construção desses textos e configuração, pela escolha, do projeto literário machadiano, assim como de uma possível relação entre a formação dessa coletânea e o ideal de “literatura brasileira” que o escritor e crítico Machado de Assis parecia ter em mente naquele momento. Também se analisou fatos relativos à história da publicação da coletânea, a fim de verificar se o editor Baptiste-Louis Garnier, que publicou tanto o Jornal das Famílias quanto a coletânea Histórias da meia noite, de 1873, teria tido alguma participação – direta ou indireta – na seleção feita pelo autor fluminense
Keywords: Assis, Machado de, 1839-1908 História da meia noite Crítica e interpretação; Garnier, Baptiste Louis 1823-1893; Literatura brasileira - História e crítica; Contos brasileiros; Short stories, Brazilian